Guidelines for the management of Helicobacter pylori infection in Italy: The III Working Group Consensus Report 2015. Issue 11 (November 2015) - Zagari, Rocco Maurizio; Romano, Marco; Ojetti, Veronica; Stockbrugger, Reinhold; Gullini, Sergio; Annibale, Bruno; Farinati, Fabio; Ierardi, Enzo; Maconi, Giovanni; Rugge, Massimo; Calabrese, Carlo; Di Mario, Francesco; et al.
Abstract Knowledge on the role of Helicobacter pylori (HP) infection is continually evolving, and treatment is becoming more challenging due to increasing bacterial resistance. Since the management of HP infection is changing, an update of the national Italian guidelines delivered in 2007 was needed. In the III Working Group Consensus Report 2015, a panel of 17 experts from several Italian regions reviewed current evidence on different topics relating to HP infection. Four working groups examined the following topics: (1) "open questions" on HP diagnosis and treatment (focusing on dyspepsia, gastro-oesophageal reflux disease, non-steroidal anti-inflammatory drugs or aspirin use and extra-gastric diseases); (2) non-invasive and invasive diagnostic tests; (3) treatment of HP infection; (4) role of HP in the prevention of gastric cancer. Statements and recommendations were discussed and a consensus reached in a final plenary session held in February 2015 in Bologna. Recommendations are based on the best current evidence to help physicians manage HP infection in Italy. The guidelines have been endorsed by the Italian Society of Gastroenterology and the Italian Society of Digestive Endoscopy.